Representações da morte por COVID-19 em charges brasileiras - Haddad, Vanessa Krunfli (2023)
This research aimed to identify and analyze the portrayals of death by Covid-19 in Brazil in four political cartoons published between April 30th, 2020 and April 3rd, 2021, by Alberto Benett, Quinho Ravelli and Daniel Lafayette. The theoretical framework used is the Cultural Semiotics, especially Iuri Lotman's conceptions of artistic text, memory and semiosphere; Cultural Studies, with a focus on Stuart Hall's reflections on representation and social tensions within culture; and the concepts of dialogism, conceived by Mikhail Bakhtin, and visual syntax, according to Donis Dondis. In the drawings we observed the re-signification of depictions that constitute the symbology of death in the West (Christian cross, open ditches, cemeteries, corpses, blood, and human skeletons), as well as the red cross (hospital symbol, in the analyzed context). Such signs composed the teargic texts in semiotic interactions with figurations of death related to Brazilian circumstances - health professionals, President Jair Bolsonaro and the Bolsonarist gesture of making a gun with the hands. We also identified the SARS-Cov-2 virus as a Covid-19 representation of death.(AU)